A functional approach to warm-up and flexibility - Swanson, J. R. (Strength and Conditioning Journal, 2006)
The warm-up is a key component in the workout or competition schedule. A well-designed warm-up will prepare the athlete physically and mentally for the intense movement associated with training or competition. Recent research suggests that a flexibility-centered warm-up may not be the most effective way to prepare the athlete for movement or to develop long-term soft tissue adaptations. The purpose of this paper is to present a functional approach to preparing athletes for movement and to developing long-term soft tissue adaptations that improve range of motion, enhance performance, and promote recovery.